On Prisons and Theatres: Santo Stefano and San Carlo - Patricia Branco (Law Text Culture, 2010)
The interconnection between law and theatre can be seen as having both specular and spectacular functions, in which space acts as a manifestation of power to shape the place or stage where law and theatre come to life and perform their spectacle. To explore this link I will use the example of the eighteenth century prison at Santo Stefano Island in Italy. The curiosity regarding this building arises from the fact that its architectural plan may have been copied from that of the San Carlo Theatre in Naples. Bentham’s Panopticon was published between the date of construction of the theatre and that of the prison. While the two buildings span the publication of the Panopticon, they also mirror each other in the panoptical direction of their gaze. I will explore these mutual influences and inversions.